Changeable Designs in Preschool Education Environments: Supporting Sensory Development and Creativity - Şahin, Belkıs Ece; DOSTOĞLU, NESLİHAN (My University, 2016)
Preschool education has special importance in the development processes of children at 3-6 age, which is the period when the foundations of individual development are established. In this period, the development of children is supported by education and appropriate environmental conditions, and in this context, the quality of the physical environment has great significance in education process. Today, the development of creative thinking of individuals is considered as one of the conditions which improve the standards of societies. Since creative thinking is significantly developed and formed in preschool period, the improvement of children's creativity is considered as one of the objectives of preschool education. In this context, proposes a design approach taking changeability as its basis to support creative thinking of children in preschool environments. This paper is based on the findings of a doctorate thesis, integrating preschool education and architecture, completed by ”. Ece Şahin at Uludağ University Department of “rchitecture, under the supervision of Prof. Dr. Neslihan Dostoğlu. The research was carried out with 30 children of age 5 in three public kindergartens in Bursa. Methods used in the study can be described as; discussions through the images of changeable toys, watching a movie about changeability, drawing a desired classroom and discussions held during a computer game where the action of change is experienced. In the research, it has been observed that changeable designs, support mental activity by stimulating feelings, encourage to think differently and to propose new ideas. Changeable designs can be consider as the products of design which trigger imagination. In this context, changeability can evaluate a parameter in designing education environments in order to support creativity in preschool years.
Keywords: Preschool Education; Child Development; Changeable Designs